Financial Feasibility of Investments in Contract Poultry Farming - Gnanakumar, P. Baba (Indian Journal of Marketing, 2007)
In the 1970s, ’80s, and ’90s, when cotton production in the South and other parts of the India dwindled as a business for farmers, people turned to poultry farming. Through cross-breeding, scientists were able to produce a fast-growing, bigger bird. In the 1990s, businesses began to take over the production of the poultry process, and the contract system in effect was born. The research paper analyse the cost and effect relationship in poultry contract farming in Coimbatore district. At present he contract farmers are earning Rs.1.50 per broiler reared. The education is not constraint for them. The yield per square feet comes around Rs.7.50 per year. The return on investment is around 11.5% in the beginning stages and 20 % in latter on stages. The farmers having number broiler rearing use the advantage of large scale operation. Since the marketing risk is covered by the integrators, the farmers are safe and earning is almost equally spread throughout the year. The researcher identified the break-even chicks to be reared and Internal Rate of Return a farmer can gain through the poultry farming. The researcher concludes that due to increase in consumption pattern of meet and export, the contract poultry farmers will reap more steady income in coming years and it is a viable alternative for uneducated farmers also.